Pemberdayaan Masyarakat oleh BUMDes Mandiri Sejahtera Tengki di Desa Tengki Kecamatan Brebes Kabupaten Brebes - Khasanah, Mafrihatul; Fauzi, Lukman Munawar; Wulandari, Widuri (Universitas Medan Area, 2024)
This research aims to determine and analyze community empowerment by BUMDes Mandiri Sejahtera Tengki in Tengki Village, Brebes District, Brebes Regency. The existing problem is that community empowerment through BUMDes carried out by the Tengki Village Government is not optimal, this can be seen from the management of BUMDes not fully involving the community. This research method is qualitative and data collection techniques are carried out using observation, interviews, and documentation. The results of this research show that the community empowerment carried out by BUMDes Mandiri Sejahtera Tengki in Tengki Village, Brebes District, Brebes Regency has not been implemented optimally in terms of several aspects, namely: Human development has not provided training or guidance to the community and only focuses on training BUMDes administrators; community business development is only involved to the extent of borrowing funds from BUMDes savings and loans; environmental development has not been able to accommodate the village's potential; and institutional development is constrained by the implementation of the vision and mission and organizational structure and work procedures so that the main tasks are only adjusted to the AD/ART. The researcher's suggestion for BUMDes Mandiri Sejahtera Tengki is to take part in training related to BUMDes, community empowerment, or training related to organizational development. Apart from that, BUMDes can also take other steps by collaborating with many parties.